The Relationship of Personal and Social Responsibility Perceptions with The Intrinsic Motivation in Physical Education - FADILAH KHAIRUNISA; YUDY HENDRAYANA; RESHANDI NUGRAHA (Universitas Pendidikan Indonesia (UPI), 2022)
Introduction: Perception is a human cognitive aspect of a person's assessment or assumption of an object or experience that appears after a person receives a stimulus that has been experienced previously to be used as a reference in acting. Purpose: The purpose of this study was to examine whether there is a relationship between perceptions of personal and social responsibility with the intrinsic motivation of grade XI students in physical education at SMAN 1 Cikampek. Methods: This study uses quantitative methods with the type of correlation research. The sampling technique used is Simple Random Sampling with a sample of 196 students in class XI. The data collection technique used a Personal and Social Responsibility Questionnaire (PSRQ) to measure personal and social responsibility perceptions and Behavioral Regulation in Exercise Questionnaire (BREQ-2) to measure intrinsic motivation. Results: The results showed that: 1) there was a relationship between perceptions of personal and social responsibility with the intrinsic motivation of class XI students in physical education at SMAN 1 Cikampek. With a Sig value of 0.00 0.05, it can be said that the variable (X1) and the variable (X2) have a relationship with the variable (Y). 2) From the table results, the coefficient number is 0.491, meaning that the level of strength of the correlation/relationship is in the Strong Enough category, and based on the table, the number of correlation coefficients is positive, namely 0.491, the direction of the relationship between the variables is positive, which means the higher the variable (X1) and ( X2), the higher the variable (Y), the same is valid if the lower the variable (X1) and (X2), the lower the variable (Y). Conclusions: There is a positive relationship between the perception of social responsibility and the perception of personal responsibility with the intrinsic motivation variable with a Sig value of 0.00 0.05.